Evolution of households’ responses to the groundwater arsenic crisis in Bangladesh: information on environmental health risks can have increasing behavioral impact over time - Balasubramanya, Soumya; Pfaff, A.; Bennear, L.; Tarozzi, A.; Ahmed, K.M.; Schoenfeld, A.; Geen, A. van (Cambridge University Press, 2014)
A national campaign of well testing through 2003 enabled households in rural Bangladesh to switch, at least for drinking water, from high-arsenic wells to neighboring lower arsenic wells. We study the well-switching dynamics over time by re-interviewing, in 2008, a randomly selected subset of households in the Araihazar region who had been interviewed in 2005. Contrary to concerns that the impact of arsenic information on switching behavior would erode over time, we find that not only was 2003–2005 switching highly persistent but also new switching by 2008 doubled the share of households at unsafe wells who had switched. The passage of time also had a cost: 22 per cent of households did not recall test results by 2008. The loss of arsenic knowledge led to staying at unsafe wells and switching from safe wells. Our results support ongoing well testing for arsenic to reinforce this beneficial information.